(untitled) (Bangladesh Journal of Medical Biochemistry, 2013)
This study was carried out in the Department of Urology, National Institute of Kidney Diseases and Urology, (NIKDU), during the period from Jan’ 09 to Dec’ 10 to assess the complications at donor site after lingual mucosal graft harvesting for urethroplasty. A total of 30 patients with mean age of 36.6 years (rang 21 to 56 years) and mean urethal stricture length of 36 mm (range 22 to 59 mm) who underwent urethroplasty for anterior urethral strictures using dorsal onlay of a lingual mucosal graft (LMG) were selected for the study. The site of the harvest graft was ventrolateral mucosal lining of the tongue. Donor site complications like pain, numbness, tightness, slurring of speech, salivatory changes and difficulty in protrusion of tongue were noted. The mean period of follow-up was 14 months (range 6-18 months). At the first postoperative day, 96% of the patients experienced pain at donor site and 26% had slurring of speech. Pain was mild to discomforting in 60% and distressing to excruciating in 37% of the patients. By third postoperative day, 22 (73%) patients were pain free, 06 (20%) suffered from mild pain and 02 (6%) suffered from discomforting pain only and none had slurring of speech. On the fifth postoperative day, only 02 (6%) patient suffered pain. By day 6 of surgery, all patients were pain free. Only 01 (3.3%) patients reported numbness which persisted during the whole period of follow up. The study showed that LMG is easy to harvest and associated with less postoperative pain, minor risk of donor site complications and without any functional or esthetic deficiency. So tongue may be the best alternative donor site for anterior urothroplasty. DOI: http://dx.doi.org/10.3329/bjmb.v5i2.13341 Bangladesh J Med Biochem 2012; 5(2): 48-52